The Sound inside the Silence Travels in the Sonic Imagination - Street, Seán (Palgrave Studies in Sound, 2019)
In this poetic exploration of the auditory imagination, the third in his series on sonic aesthetics, Seán Street peoples silence with sound, travelling through time and space to the distant past, the infinite future and the shadow lands of the inner psyche. Our mind is a canvas on which the colours of the sound world leave permanent impressions. It is the root of all listening.